Impact of land use on microbial communities in the Great Bend Prairie Aquifer - Richardson, Christina R. (Kansas State University, 2019)
The High Plains aquifer is a vital source of irrigation and drinking water in the central United States. Aquifer geochemistry and water quality can be significantly affected by microbially mediated redox reactions. Therefore, it is important to understand how environmental controls on aquifer microbial communities affect the health of the aquifer. This study examines the relationship between land use and aquifer microbiology in the Great Bend Prairie aquifer, a portion of the High Plains aquifer in south-central Kansas. In the summer of 2018, we collected samples from soils of different land use near groundwater monitoring wells that were sampled two years prior. The soil samples were collected in replicates of four at each well site, and the groundwater was sampled from wells screened in the shallow and deep aquifer at each site. Results demonstrate significant variation in nitrate levels with land use in both soils and groundwater. Soil extractable NO₃-N in irrigated crop soils is significantly higher (86.05 mg/kg) than in pasture (3.84 mg/kg) and non-irrigated crop (29.48 mg/kg) soils on average. Shallow wells below crop soils contain average NO₃-N concentrations three times higher than those of the shallow wells below pasture soils and of the deep wells, at 18 mg/L. Coupled with this impact, microbial community composition also varies significantly with land use in both soils and groundwater. Our statistical analysis shows that NO₃-N and soil microbial communities are significantly correlated, with land use as the best defining factor in soil community similarity. Groundwater microbial communities were significantly correlated with land use and geographic markers, with well depth as the best defining factor in groundwater microbial community. Specifically, the aquifer contains many genera capable of participating in the nitrification and denitrification processes, including genera within bacterial orders Nitrospirales (nitrification) and Pseudomonadales (denitrification), as well as archaeal phylum Crenarchaeota (nitrification and nitrite reduction). Shallow crop wells have the highest average relative abundances of Pseudomonadales (12.14% ) and Nitrospirales (7.03%), compared to other wells. Deep crop wells have the highest average relative abundances of Crenarchaeota (3.25%). Taken together, our results show that land use not only affects the chemistry and microbiology of soils but also the underlying water table aquifer. These findings advance our understanding of environmental controls on aquifer microbiology.
Keywords: High Plains aquifer; Microbiology; Groundwater; Soil; Aquifer; Land use impact on microbiology